Simulation of Semiconductor Processes and Devices 2007
DOI: 10.1007/978-3-211-72861-1_66
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of AlGaN/GaN HEMTs’ Breakdown Voltage Enhancement Using Grating Field Plates

Abstract: Two dimensional physical-based device simulations (Silvaco -"Atlas") of breakdown voltage (V br ) effect in AlGaN/GaN HEMTs (high electron mobility transistors) on silicon carbide (4H-SiC) device are preformed. The influence of novel single layer grating field plates (FPs), consisting of gate connected fingers and floating fingers, on V br , obtained via the electric field distribution in the AlGaN layer is studied. We have found that the grating FPs reduce the electric field peaks and efficiently distribute t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Bahat-Treidel et al [20] has reported on the simulations of AlGaN/GaN HEMT breakdown voltage. However, it is debatable whether to adopt the Albrecht low field mobility model, which is not very accurate for III-N compounds.…”
Section: Breakdown Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bahat-Treidel et al [20] has reported on the simulations of AlGaN/GaN HEMT breakdown voltage. However, it is debatable whether to adopt the Albrecht low field mobility model, which is not very accurate for III-N compounds.…”
Section: Breakdown Characteristicsmentioning
confidence: 99%
“…In Ref. [20], it was proposed that grating field plates could enhance the AlGaN/GaN HEMT breakdown voltage, which can also be ascribed to the extension of equipotential lines. The difference is that grating field plates provide multiple sources to extend the equipotential lines.…”
Section: Breakdown Characteristicsmentioning
confidence: 99%
“…In the future we will be able to calibrate the models more thoroughly with those results. An extensive calibration process has been performed by Bahat-Treidel 5 and that process highlights some of the more critical models that can be used for more accurate results. We have followed those recommendations in lieu of device results for now.…”
Section: Device Structure and Simulation Methodologymentioning
confidence: 99%
“…In order to accommodate device scale, breakdown is alternatively defined as the voltage at which the drain leakage current exceeds 1 mA/mm. 5,22,23 The definition used for breakdown voltage in our simulations has been modified further to include area factor. This change is necessary to accommodate how the plot of breakdown current will change shape when altering lateral dimensions.…”
Section: Simulation Methodology and Simulationmentioning
confidence: 99%
“…et al first proposed the FP-G and achieved a high V BD of 570 V, but resulting in severe degradation of frequency characteristics [6]. Since then, multiple grating FP-G [7,8] and novel FP-G structures [9,10] have been invented to reduce the frequency 2 of 11 degradation. Relevant analytical models [11,12] and reliability improvement [13] were also reported, providing a deeper insight into the relationship between FPs and V BD .…”
Section: Introductionmentioning
confidence: 99%